The clinical judgment of nurses in fall risk assessment - Almeida,Fabiana Maria de (2018)
OBJECTIVE: This study aimed to describe the clinical judgment of nurses in fall risk assessment for hospitalized older adults. METHOD: This exploratory, descriptive study with a qualitative approach was conducted in Unified Health System hospitals in Cuiabá, MT, Brazil. A total of 18 nurses in medical and surgical clinics participated. The data were collected from March to August 2013 using a semi-structured interview and were assessed through thematic analysis based on Tanner’s clinical judgment model (2006). RESULTS: Fall risk evaluation in older adults is performed unsystematically and superficially. The nurses considered the most appropriate time to collect data and assess the fall risk of older patients to be at patient admission, although shift changes, patient visits, conversations or information exchange with hospital reception staff contributed. Although the signs or factors of patient fall risk were identified, inferences were produced and opinions were issued, the inferences were not validated. CONCLUSIONS: The two initial stages of CJ — recognition and interpretation — are unsystematic, incomplete and inconsistent, which can lead to inaccurate assessment of fall risk among hospitalized older adults.